Requirement analysis to design the knowledge-based system for long jump coaching - Teerawat Kamnardsiri (2019)
© 2019 Inderscience Enterprises Ltd. This paper presents the requirement for coaching the long jump of sports schools in Thailand. Moreover, a knowledge-based system (KBS) was designed for improving the long jump of athletes. Telephone and face-to-face interview approaches were used for collecting data from sports schools. There were 11 interview questions to investigate the requirement. MAXQDA 12 was employed to generate code and analyse data from interviewees. The results demonstrated that one of the most significant problems of coaching was the lacking of the system for analysis and suggestion. The framework, furthermore, was designed by experts using the knowledge engineering technique to create IF-THEN rules and an algorithm of all phases of the long jump biomechanics. In conclusion, there were many issues of requirements, for instance, all of the coaches required some systems for analysis and suggestion to improve the long jump skills. For the future works, the decision making algorithms of the system should be developed by using computer vision techniques.